FOREIGN DEBT OF RUSSIA: DEBT DEPENDENCE AND IMPERIALIST RENT - Alexandra A. Zhdanovskaya (Plekhanov Russian University of Economics, 2018)
The article analyzes the problem of Russia foreign debt from the point of view of the world-system approach as a form of economic dependence.  The debt dependence of Russia is revealed in increase in the foreign  debt volume and its service and in the trend of negative net-transfer in  favour of creditors. The author identifies the volumes of imperialist rent, which is passed by Russia to countries of the center in respect to foreign debt. It is pointed out that debt dependence is based on dependence in  the field of production and trade, thus its overcoming is possible only with simultaneous overcoming of different forms of economic  dependence.